Pekerjaan Sosial dalam Pengembangan Masyarakat: Pendekatan Pekerjaan Sosial Pembangunan - Huraerah, Abu (Jurnal Publisitas, 2024)
Purpose of the study is to describe social work in community development which is based on the development social work approach. This research method uses literature study by referring to scientific journals and books as references. Social work carried out in Indonesia is generally still social work as practiced in the United States or Europe. This approach is not suitable for Indonesian society, because the problems experienced by Indonesian society in general are more socio-economic than social psychological problems. Therefore, it is advisable to use developmental social work. Developmental social work is more appropriate for developing countries. In this developmental social work approach, social workers can develop human capital, social capital, and engage clients in productive work.